Canada's family violence initiative: partnerships - Elaine Scott
Under Canada's four-year, $136 million Family Violence Initiative, the federal government is calling upon all Canadians to work in partnerships towards the elimination of family violence - child abuse, violence against women, and elder (senior) abuse. Family violence is a complex problem and requires the efforts of all Canadians to resolve it. One of the key themes of the Initiative - a multidisciplinary approach to the problem of family violence - is reflected in the selection and development of projects. Activities funded by the seven federal departments and agencies involved in the Initiative emphasize partnerships with the professional, voluntary, corporate, non-government and government sectors.